FANN AL-QAUL BY AMIN AL-KHOULI AND ITS CONNECTION TO STYLISTIC STUDY / ÙÙ† Ø§Ù„Ù‚ÙˆÙ„ Ù„Ø£Ù…ÙŠÙ† Ø§Ù„Ø®ÙˆÙ„ÙŠ ÙˆØ¹Ù„Ø§Ù‚ØªÙ‡ Ø¨Ø§Ù„Ø£Ø³Ù„ÙˆØ¨ÙŠØ© - Mohammad Izdiyan Muttaqin (IAIN Batusangkar, Indonesia, 2022)
Amin al-Khouli is the pioneer of Balaghah renewal in modern era. Balaghah renewal that is called Fann al-Qaul (Art of Speaking) appeared in a period close to the appearance period of stylistic study in Europe. The purpose of this research is to reveal the connection between Amin al-Khouli’s ideas about Balaghah renewal in his book Fann al-Qaul and stylistic study. This was a library research. Researcher relied on the book Fann al-Qaul by Amin Al-Khouli to identify his ideas about Balaghah renewal and a book by Pierre Giraud entitled al-Uslubiyyah (Stylistic), translated by Mundzir al-Ayasyi to identify basic theories of stylistic. Results showed that there was a strong connection between Fann al-Qaul and stylistic study that was represented in following aspects: 1) attention to word stylistic aspect, 2) attention to internal meaning of texts, 3) attention to speakers’ condition, and 4) emphasizes the freedom in creating and criticizing literary works from the limitations of ancient rules.